Editoriale: Sviluppo di strumenti valutativi semplici per la individuazione delle sorgenti di rischio lavorativo e la prevenzione dei disturbi muscolo scheletrici: esperienze di applicazione nel lavoro artigianale e nella piccola impresa / Development of simple tools for risk identification and prevention of WMSDs (Work related Muscular- Skeletal Disorders): application experience in small and craft industries - Colombini, D.; Occhipinti, E. (La Medicina del Lavoro, 2011)
«Development of simple tools for risk identification and prevention of WMSDs (Work related Muscular-Skeletal Disorders): application experience in small and craft industries ». When studying WMSDs, multiple factors of different nature (mechanical, organizational, psychosocial, individual) and their interrelationship are considered relevant; consequently, the need for a “holistic” approach to MSD prevention was established. However, in recent years, considering the widespread presence of WMSDs in various work contexts there is a strong demand from OSH agencies and operators to develop “simple” tools for risk assessment and management, usable also by non-experts both in developed and developing countries, and in particular in craft industries and SME (small-medium enterprises). The World Health Organization (WHO) promoted the development of “toolkits” for different occupational risks and diseases; in outlining a toolkit (for WMSDs prevention), WHO defines this as “a set of practical risk assessment procedures and related management guidance documents, including advice on simple risk control options”. The “Ergonomics of Posture and Movement” Research Unit (EPM) is very much involved in the WHO project for developing a “toolkit for MSD prevention”(as well as in similar issues promoted by ISO or UE); attention was consequently focused on craft industries, small enterprises and “difficult” work sectors (i.e. agriculture, fisheries, construction). In these sectors simple tools, procedures and software were developed and applied, that could facilitate WMSDs risk assessment and management. This issue of “La Medicina del Lavoro” is entirely devoted to selected papers regarding the above proposals and experience, especially in craft industries. The opening paper is a basic methodological contribution presenting a procedure and a tool (with relative software) that is useful for the identification of a number of occupational risks by means of special “key-enters”; the same tool, with special regard to WMSDs, defines criteria for a “quick risk assessment” which is mainly aimed at identifying 3 possible conditions: Acceptable (no remedial actions needed); High risk present (redesign is urgently needed); More detailed analysis is necessary, using proper tools for risk estimation (derived from recognized literature, international standards and/or guidelines) A series of practical applications in different craft industry contexts are then presented: the selection of the papers took into account that, apart from producing specific results on “risk mapping”, they gave a detailed analysis of “production cycles” in work sectors that are often “neglected” in OSH literature. Other application experience in similar work contexts using a quite similar approach will, for reasons of space, be reported in future volumes of this journal. Finally, in the web sites of the journal (http://www.lamedicinadellavoro.it/) and of the EPM Research Unit (http://www.epmresearch.org), the reader will find (only on-line) papers and information regarding updates on the use of the “OCRA Checklist” that is now also proposed in a simpler version (OCRA mini-checklist) that can be applied specially in the sectors considered here and whenever production is “variable”.